2021
DOI: 10.1093/bjsopen/zrab038
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of microscopically non-radical oesophagectomy for oesophageal and oesophagogastric junctional cancer: nationwide cohort study

Abstract: Background Microscopically non-radical (R1) oesophageal cancer resection has been associated with worse survival. The aim of this study was to identify risk factors for R1 resection and to investigate how this affects long-term survival. Methods The Swedish National Register for Oesophageal and Gastric Cancer was used to identify all patients who underwent oesophageal cancer resection with curative intent between 2006 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Upon examining the impacts of these surgical techniques on the criteria defining TBO, it was observed that patients undergoing RE experienced fewer major complications than those treated with VATE. More critically, RE was associated with a higher likelihood of achieving margin-negative resections and an increased count of harvested lymph nodes—two factors that are known to correlate with a more favorable prognosis [ 30 , 31 , 32 , 33 ]. Taken together, these findings suggest that RE not only potentially eases postoperative recovery, but also contributes to superior oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Upon examining the impacts of these surgical techniques on the criteria defining TBO, it was observed that patients undergoing RE experienced fewer major complications than those treated with VATE. More critically, RE was associated with a higher likelihood of achieving margin-negative resections and an increased count of harvested lymph nodes—two factors that are known to correlate with a more favorable prognosis [ 30 , 31 , 32 , 33 ]. Taken together, these findings suggest that RE not only potentially eases postoperative recovery, but also contributes to superior oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative prognosis is highly dependent on the extent of locoregional tumor clearance in addition to pathological stage, particularly LN spread [13,26,27]. Previous studies showed that the median survival of non-curative esophagogastric cancer was 5.1 months [28] and 1-and 3-year OS rates of patients with cT4 for palliative resections (R1/2) were 8.5% and 0%, respectively [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, curative esophagectomy is not always possible due to invasion of adjacent organs, intraoperative distant metastases, or positive resection margins [12,13]. A previous study using the Netherlands Cancer Registry showed that failure-to-cure was noted in 15% of surgically treated patients, and the most common reason for non-curative resection is an invasion into adjacent organs (T4b) [14].…”
Section: Introductionmentioning
confidence: 99%